Poly(l‐glutamic acid)‐based micellar hydrogel with improved mechanical performance and proteins loading. Issue 17 (16th August 2019) - Yu, Xi; Zhang, Kunxi; Kong, Xiaobo; Yin, Jingbo
ABSTRACT: Soft tissues, such as fat and skin, present high flexibility and are capable of withstanding large deformation in various functions. Hydrogels that can resemble the mechanical performance of soft tissue are unique and widely demanded. In this study, micellar hydrogels based on biocompatible poly(l ‐glutamic acid) (PLGA) were designed with the enhanced capacity to bear large deformation. Amphipathic triblock copolymer poly(ethylene glycol) acrylate‐ co ‐poly(ε‐caprolactone)‐ co ‐poly (ethylene glycol) acrylate (APEG‐PCL‐APEG) with two terminal double bonds was synthesized and self‐assembled into micelles. At the same time, graft copolymers, poly(l ‐glutamic acid)‐ g ‐hydroxyethyl methacrylate (PLGA‐ g ‐HEMA) with double bonds were synthesized. APEG‐PCL‐APEG micelles and PLGA‐ g ‐HEMA were mixed to construct micellar hydrogel via radical polymerization. The crystalline structure and hydrophobic aggregation of copolymers (APEG‐PCL‐APEG) were found to associate with PCL molecular weight. Due to the hydrophobic stress dissipation and crystalline structure of the micelles, the softness and toughness of hydrogels were promoted, exhibiting a 25% increase in ultimate strain. Moreover, the micellar hydrogels were able to load proteins with long‐term retention. In addition, under dynamic mechanical stimulation, the release of proteins could be accelerated. Besides, the micellar hydrogels also supported rabbit adipose‐derived stem cells (rASCs) growth, thus exhibiting the potential toward soft tissue engineering. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2019, 57, 1115–1125 Abstract : To develop a hydrogel with good compressibility and biocompatibility, poly(l ‐glutamic acid)‐based micellar hydrogels were constructed. The micelles were used to consume the stress due to the hydrophobic interaction as the external load was exerted on the hydrogels. The crystalline structure of the micelles also endowed the hydrogels with a certain amount of strength to keep their structural integrity. Furthermore, bovine serum albumin, a model protein, was loaded into the micelles. The hydrogels supported the growth of rASCs.